Fatal outcome of suspected delayed-onset malignant hyperthermia in an infant with phocomelia: challenges in diagnosis and management - Sharma, Sekhar Jyoti; Deori, Pori; Bora, Bikash Bhaskar; Khound, Murchana; Pao, Mritunjay (International Journal Of Community Medicine And Public Health, 2024)
Malignant hyperthermia (MH) is a rare, life-threatening condition triggered by certain anesthetic agents, characterized by rapid onset of hypermetabolism, muscle rigidity, hyperthermia, and metabolic acidosis. Timely identification and the administration of dantrolene are pivotal in preventing fatal outcomes. We report the case of a 10-month-old male infant with phocomelia who developed delayed-onset MH following an otherwise uneventful herniotomy. The infant presented with seizures and an acute rise in body temperature (106°F) three hours post-surgery, suggesting a diagnosis of MH. Despite immediate administration of anticonvulsants and the initiation of aggressive cooling protocols, the seizures persisted, necessitating intubation, paralysis, and thiopentone infusion. Laboratory investigations showed severe metabolic acidosis and signs of rhabdomyolysis, such as reddish urine. A CT scan later revealed brain edema. Management was further complicated by the unavailability of dantrolene, the definitive treatment for MH, leading to a progressive decline in the patient’s condition and, eventually, multi-organ dysfunction and death. This case highlights the atypical presentation of delayed-onset MH in a pediatric patient with congenital anomalies and underscores the critical need for prompt recognition, effective management strategies, and the availability of essential treatments like dantrolene. It also emphasizes the importance of preparedness and adaptability among clinicians to manage rare, life-threatening conditions effectively and improve patient outcomes.